Investigation of Learning Style Preferences of Business Students in Saudi Arabia- using VAK Assessment Model (Global Journal of Management and Business Research, 2018)
This study focuses on investigation of learning style preferences of business students who enrolled in two different set of course modules; descriptive and mathematical. This study is crosssectional research depends on primary data gathered from a business student who studies in a state university in Saudi Arabia. The purposive sampling methods used to select the sample and VAK modality questionnaire was used to collect data. The Cronbach's alpha for three styles; visual learner, auditory learner, kinesthetic learners was respectively 0.83, 0.80, and 0.77. Percentages were calculated to determine students' desirable learning style, and chi-square test and independent sample t-test were conducted to discover the difference between learning style of descriptive courses and mathematical courses. It has revealed that both groups of students prefer multimodal more than unimodal. The highest unimodal preference was the visual style for both groups of students. Independent sample t-test results showed that there was no difference between the two groups of students.
Keywords: VAK learning styles model; visual learner; auditory learner; kinesthetic learners